Motivația intrinsecă - predictor al implicării academice a studenților [Articol] - Momanu, Mirela-Claudia; Potâng, Angela (CEP USM, 2024)
Motivation represents a long-researched construct, as it is put at the service of obtaining high performance in all areas of human activity, representing a higher level of individual goal achievement within the various actions performed. In this research we set out to specifically identify the influence of intrinsic motivation, through the prism of its facets intrinsic motivation for knowledge, intrinsic motivation for achievement and intrinsic motivation to stimulate exploration, which bring a significant contribution to the achievement of aspirational progress and which can have a determining role on the involvement of students in the academic environment. We expect to identify certain aspects related to intrinsic motivation that have a large weight within this influence and that can generate an increase in academic involvement and, if possible, to quantify the extent to which the intrinsic motivation for knowledge, intrinsic motivation for achievement and intrinsic motivation to stimulate exploration respectively could represent factors of the potential of students’ academic engagement and performance.
INTRINSIC MOTIVATION - PREDICTOR OF ACADEMIC INVOLVEMENT OF STUDENTS
Keywords: academic engagement; education; intrinsic motivation